2011
DOI: 10.1007/s11684-010-0104-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-etching adhesives: possible new pulp capping agents to vital pulp therapy

Abstract: Pulp capping is one of the solving for keeping vital pulp in the case of dentin caries, reversible pulpitis or traumatic pulp exposure. The presence of bacteria on the cavity walls or in the pulp was the major factor that leads to the failure of pulp capping. Traditional pulp capping agent, calcium hydroxide, may not prevent microleakage. Selfetching system is a newly developed adhesive system, which could provide less microleakage and would not break down or dissolve, preventing the oral fluids and bacteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Suppression of bacterial activity is considered a key modality in controlling dental caries and periodontal diseases. Various strategies have been developed, including inhibition of protease activity [ 13 , 14 ] and the application of antibacterial dental materials [ 15 , 16 ]. Recently, the antibacterial activity of a composite resin containing prereacted glass ionomer (S-PRG) filler was revealed [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of bacterial activity is considered a key modality in controlling dental caries and periodontal diseases. Various strategies have been developed, including inhibition of protease activity [ 13 , 14 ] and the application of antibacterial dental materials [ 15 , 16 ]. Recently, the antibacterial activity of a composite resin containing prereacted glass ionomer (S-PRG) filler was revealed [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is less relevant for the placement of the material, as CPT is conducted under dental dam isolation, which reduces the potential for washing out the material during its placement [ 13 ]. However, the breakdown of the material over time within the pulp chamber could lead to microleaks in the absence of a good orifice barrier and permanent restoration [ 19 ]. Therefore, future studies may look at incorporating a crosslinking agent into the formulation to improve the structural integrity of the experimental pulp-capping material.…”
Section: Discussionmentioning
confidence: 99%
“…Current investigations have also shown that even low concentrations of triethylene glycol dimethacrylate (TEGDMA), a compound found in dentin bonding agents, inhibits dental pulp cells from mineralization and reparative dentin formation . However, some promise has been shown using adhesive resins combined with additives (growth factors), including synthetic peptides derived from dental matrix protein, hydroxyapatite powder, calcium chloride (CaCl 2 ) , and antibacterial agents such as 12‐methacryloyloxydodecylpyridinium bromide (MDPB) . Although bonding agents do not promote a favorable environment for pulp repair and bridge formation, they can provide excellent seals when used in conjunction with composites for coronal restorations in vital pulp therapy.…”
Section: Contemporary Pulp Therapy Materialsmentioning
confidence: 99%